The role of pH in heavy metal contamination of urban soil - Kazlauskaitė-Jadzevičė, Asta; Volungevičius, Jonas; Gregorauskienė, Virginija; Marcinkonis, Saulius (Journal of Environmental Engineering and Landscape Management, 2014)
The aim of this study to assess interdependence between urban soil pH and its accumulation of heavy metals. The article meant to be a contribution to a better knowledge of peculiarities and diagnostics of urban soil and its anthropogenic transformation. The hypothesis assumes that relationship between urban soil pH and its accumulation of heavy metals may be determined by the origin and age of parent material as well as the nature and degree of the anthropogenic impact. The spatial variability of topsoil pH level was performed in 100 points in eldership of Šnipiškės of the city Vilnius. Laboratory analysis was based on ISO 10390:2005. Samples were collected from 20 cm topsoil layer in the same sampling points where have been analysed concentrations of topsoil chemical elements using optical atomic emission spectrophotometry. The contamination of urban soils exhibits somewhat different compared to agricultural soils. In contradiction to earlier studies in Lithuanian agricultural soils where strong correlation between soil pH and Cr, Cd, Pb, Ni, Cu and Zd found, the conducted analysis shows a statistically reliable, but very weak (<0.3) correlation between the soil pH and concentration of contaminants. The proof to this correlation is provided by an existing relationship between pH and the concentration of copper (r = 0.20), mercury (r = 0.15), strontium (r = –0.12) and the overall contamination index (r = 0.12). The applied statistical analysis, however, failed to reveal the nature of interdependence between the soil pH and its contamination with studied heavy metals there concentration of contaminant chemical elements depends on the pH range of the soil and, conversely, the chemical reactivity of the soil changes affect on the concentration of studied chemical elements. First published online: 03 Jun 2014